New Aspects of Polymer Characterization by Dynamic Light Scattering - Walther Burchard (CHIMIA)
Can macromolecules be seen moving? No doubt, twenty years ago the answer would have been a definite «No». Today we are more inclined to answer positively, assuming we accept the observation of scattered light as a kind of seeing. The new capability of watching the motion of molecules, without exerting an external force on the system, is a typical feature of our time with its high technology in electronics and the construction of fast digital computers. Once the new technique was understood, the various aspects and possibilities were immediately anticipated by scientists. These ideas remained fairly speculative for several years, but now a stage has been reached where some of the experiments suggested earlier have since been tested and where further applications can be foreseen. Most exciting is probably the prospect of determining viscoelastic properties in some favourable cases. The present article provides an introduction to the principles of this fairly new technique. The power of the method is illustrated by two simple examples and, finally, some problems of practical interest are discussed.